Clinical experience with adalimumab biosimilar imraldi in hidradenitis suppurativa. Issue 6 (19th October 2020) - Ricceri, Federica; Rosi, Elia; Di Cesare, Antonella; Pescitelli, Leonardo; Fastame, Maria Thais; Prignano, Francesca
Abstract: Adalimumab is the only biologic therapy approved for the treatment of patients with hidradenitis suppurativa, a chronic and disabling skin condition. To date, there are no studies in the literature about the effectiveness of adalimumab biosimilar SB5 in hidradenitis suppurativa. The aim of this study was to evaluate its efficacy and safety. A retrospective observational study was performed in hidradenitis suppurativa adalimumab naive patients and in patients who were switched from the adalimumab originator. Eleven patients were included in the study. Our results support adalimumab SB5 as an effective and well tolerated drug, with a good interchangeability with its originator also for the treatment of hidradenitis suppurativa.